2015
DOI: 10.1108/amhid-04-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual disability, personality disorder and offending: a systematic review

Abstract: Purpose -This review seeks to systematically review studies where personality disorder has been explored as a descriptive or possible predictive factor in offending behaviour in people with an intellectual disability. The papar aims to discuss this issue. Design/methodology/approach -A systematic search of several databases was conducted and 15 studies met the inclusion criteria and were included in this review. Findings -Methodological limitations and problems in accurate diagnosis within this client group pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The current knowledge on the impact of PD diagnoses in people with intellectual disability remains quite scarce, with most of the research to date focusing predominantly on epidemiology and prevalence rates (Flynn et al, 2002), especially within forensic settings (Alexander et al, 2012; Rayner et al, 2015). The qualitative literature around this topic appears to be even sparser, with little to no insight currently available on the subjective experience of healthcare professionals (HCPs) working with these presentations.…”
Section: Introductionmentioning
confidence: 99%
“…The current knowledge on the impact of PD diagnoses in people with intellectual disability remains quite scarce, with most of the research to date focusing predominantly on epidemiology and prevalence rates (Flynn et al, 2002), especially within forensic settings (Alexander et al, 2012; Rayner et al, 2015). The qualitative literature around this topic appears to be even sparser, with little to no insight currently available on the subjective experience of healthcare professionals (HCPs) working with these presentations.…”
Section: Introductionmentioning
confidence: 99%
“…Within inpatient services rates of between 22 and 92 per cent have been reported (Alexander and Cooray, 2003). Studies using forensic populations report that 1.4-56 per cent of ID offenders meet criteria for a PD (Rayner et al, 2015). Within forensic inpatient services the prevalence of PD's has been reported as 56 per cent for high secure settings, 26.2 per cent for medium/low secure settings, with the overall average being reported as 39.3 per cent (Lindsay et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Within forensic inpatient services the prevalence of PD's has been reported as 56 per cent for high secure settings, 26.2 per cent for medium/low secure settings, with the overall average being reported as 39.3 per cent (Lindsay et al, 2006). Borderline and anti-social PD are the most common PD diagnoses in ID offender populations (Rayner et al, 2015) and women are more likely to be diagnosed with a PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated in the first paragraph, a diagnostic system should enable prediction of certain related factors and since PD has been strongly associated with violence in offender populations the prediction of violence (Monahan et al , 2001; Harris et al , 1993) has been focussed on in this study. The relationship between PD and offending was reinforced by the review on PD and IDD presented by Rayner et al (2015) when they found that the presence of PD in someone with IDD is associated with more dangerous offending. The present study is a comparison of the predictive value of these two methods in relation to future violence.…”
mentioning
confidence: 99%